FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI RSKDIA PERTIWI MAKASSAR - Ayatullah Harun; Jumriani Jumriani (Politeknik Kesehatan Kemenkes Mamuju, 2017)
Colostrum represents the first fluid that secreted by the breast gland, containing tissue debris and residual material in the alveoli and ducts of the breast glands pre- and post-puerperium. It is also viscous liquid with yellowish color and more yellow than mature milk (Wulandari & Handayani, 2011). This research aimed to determine the relationship of mother knowledge, family support and health officers by giving colostrum at RSKDIA Pertiwi Makassar. The methods of research by using anaytical design with cross sectional study apparoach, the sample of research is post-partum mother as many as 122 mothers. The result of research indicates that there is significant correlation between mother’s knowledge with the giving of colostrum for newborn with p-value = 0.014 < α = 0.05, there is no significant correlation between family support and the giving of colostrum with p-value = 0.79 > α = 0.05 and there is no correlation between health officer support with the giving of colostrum with p-value = 0.283 > α = 0.05. It can be concluded that there is a relationship between mother’s knowledge with the giving of colostrum and there is no relationship between family support, and health officer support with the giving of colostrum. It is expected that mothers can increase their knowledge about colostrum delivery for newborn by following counseling of health officer as well as increasing the role of health officer by giving health program especially in improving the understanding of communities about the importance of colostrum.